High prevalence of undernutrition among male brick kiln workers of Murshidabad District, West Bengal, India: A comparison of body mass index and mid-upper arm circumference - Mihir Ghosh; Kaushik Bose (Al Ameen Medical College, 2016)
Background: Undernutrition among rural Muslim population, especially the brick-kiln-workers may be a major health problem in India. Material and Methods: A cross-sectional study of 505 male adult brick-kiln workers of Murshidabad district, West Bengal was conducted. The body mass index (BMI) and mid-upper-arm circumference (MUAC) were used to evaluate CED (BMI < 18.5 kg/m2). To assess nutritional status and to compare the utility of two different anthropometric indicators of chronic energy deficiency (CED) among adult male brick-kiln workers. Results and Conclusion: BMI based prevalence of CED was 25.00% while under nutrition based on MUAC < 23.0 cm was 23.40%. Both these prevalence comes under the high-prevalence category (25.00%) indicating a serious situation according to World Health Organization recommendations. Among the low MUAC (<23.0 cm) individuals, the rate of CED was significantly (p<0.001, x2 =169.40) higher (70.30%) than among normal MUAC (≥ 23.0 cm) individuals (29.70%).This occupational group was facing severe nutritional stress. With limited resources and in the absence of skilled manpower, it may be more appropriate to use MUAC for human population surveys, particularly among adults of developing countries.